PROPTYCHOPTERINA (DIPTERA: EOPTYCHOPTERIDAE) FROM THE JURASSIC OF NORTHEASTERN CHINA - Lin Q.-B.; Lukashevich E.D. (My University, 2006)
A complete well-preserved male fly from the Jurassic of Daohugou locality (Northeastern China) is described as Proptychopterina opinata sp. nov. The distribution of Proptychopterina is discussed, this genus is re-diagnosed, and a key to species is provided based on the wings. © Pleiades Publishing, Inc. 2006.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская